3D–printing AIE stereolithography resins with real−time monitored printing process to fabricate fluorescent objects. (1st February 2021) - Ji, Jiujiang; Wang, Mengshi; Hu, Miaomiao; Mao, Liucheng; Wang, Qigang; Zhou, Wuyi; Tian, Mei; Yuan, Jinying; Hu, Kun; Wei, Yen
Abstract: Two types of aggregation−induced emission (AIE) stereolithography resins have been prepared. The AIE thermoset photocurable resin is made by covalently crosslinking of tetrakis (4–aminophenyl) ethene, bisphenol F epoxy resin (BPF) and methylacrylic acid (MAA). However, the AIE thermoplastic photocurable resin with "OFF–ON" fluorescence response is prepared by doping the AIE luminogens to the polymers rather than covalently crosslinking. The 3D printing process of these photopolymers can be continuously monitored according to the change of the fluorescence intensity for the first time. Before printing, the solution is non−fluorescent, during the printing process, fluorescence appears because aggregation of AIE moieties, and the printed objects are highly fluorescent after photosetting. So, this work offers an important tool for measuring printing and photo−curing processes. Furthermore, the colorful models can be obtained by mixing and curing them in different proportions just like mixing pigments and the fluorescence has also been found sensitive to the phase transitions (e.g., glass transition temperature, Tg ) of materials. Finally, the curing process of the prepared AIE stereolithography resins is helpful to understand the AIE mechanism and have a potential to expand the application of the AIE molecules. Graphical abstract: Image 1 Highlights: Two types of aggregation−induced emission (AIE) stereolithography resins have been prepared for the first time. Monitoring 3D printing process according to the change of the fluorescence intensity. The phase transitions (e.g., glass transition temperature, Tg ) of materials could be detected by analyzed the fluorescence. The colorful models could be obtained by mixing and curing AIE stereolithography resins in different proportions.